Genetic characterization of rhizobia isolated from Amazonas soils based on the technique of PCR-RFLP - Chagas Júnior, A. F.; Oliveira, Luiz Antonio de; Oliveira, Arlem Nascimento de (Semina:Ciencias Agrarias, 2009)
Few are the details concerning the molecular characterization of native rhizobia isolates from Amazonas soils. The aim of the present study was the genetic characterization of rhizobia isolated from nodules of cowpea using the method PCR-RFLP of the ribosome genes 16S rRNA and the restriction enzymes HinfI, MspI, and MboI. The analysis included 20 native isolates and ten reference strains from different origins. The results indicated a great genetic variability with the formation of eight groups in one dendrogram with a varied level of similarity.
Caracterização genética de rizóbio isolados de solos no Amazonas baseada na técnica de PCR-RFLP